Nilai-Nilai Pendidikan dalam Hadis Belajar dan Mengajarkan al-Qur'an (Analisis Kata َتعلم-يتعلم) تَعَلّم) dalam Hadis) - - Surahman (Akademika: Jurnal Keagamaan dan Pendidikan, 2018)
The study of the Qur’an is an obligation of parents to their children since they are at an early age. When parents do not have the ability to teach the Qur’an to their children directly, then the solution is to submit the study of the Qur’an to others or teachers who have the ability to teach the Qur’an. This is done so that children from an early age already know and love the Qur’an. Love reading al-Qur’an is highly recommended. To strengthen the obligation to learn and teach the Qur’an, it has been widely recorded in the traditions of the Prophet Muhammad SAW.___________________Keywords: Hadith, The Values of Qur’anic Teaching, Learning Education